Pengembangan bahan ajar modul berbasis discovery learning pada materi laju reaksi - Leady Tresia Silaban; Marudut Sinaga (ARKA INSTITUTE, 2022)
This research aims to (1) knowing the results of a chemical study on the action based reaction materials used at school by BSNP standards,(2) knowing that the modules on discovery learning on the action-based reaction rate matter are appropriate for media experts and materials experts,(3) knowing the results of student learning after being given the discovery learning module on reaction rate materials. (4) know students' responses to the discovery learning based modules on reaction rate materials. Research results from an average of 81% of those produced from teaching materials analysis have both the strenghts and deformityof content, language worthiness, presentation and feasibility of expertise. Average pretest class experiment in 57,25%. Whereas the average score of 83,5% experimental posttest class. N-gain values a normalized chemical student experiment class based on the percentage of that is 83,82%. Student response or satisfaction percentages of deveoloped modules are acquired on an averaged of 93%, which could be concluded that the developedment of the taught materials the discovery learning based modules on a action-based reaction rare matter is higher than the minimum criteria (KKM) set. T_count more that t_table (8,747 more that 1,685) and H0 is therefore denied and Ha received. Thus it may be concluded that the there is an impact on the development of taught materials the discovery learning based modules on action on reaction materials.